Evaluasi Ketercapaian Layanan Bimbingan dan Konseling dalam Implementasi Kurikulum Merdeka di SMAN 2 Lengayang - Sandra, Rober; Syukur, Yarmis; T, Taufik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to assess the effectiveness of guidance and counseling (BK) services in implementing the Independent Curriculum at SMAN 2 Lengayang. BK services consist of four main aspects, namely basic services, responsive services, individual planning services, and system support services. The evaluation was conducted to measure the extent to which these services have been implemented in accordance with the needs of students and the direction of the Independent Curriculum policy which emphasizes the development of Pancasila student profiles. The method used in this study is a descriptive quantitative approach with data collection through questionnaires and interviews with BK teachers and students. The results of the study showed that overall, the effectiveness of BK services was in the fairly good category, although there were still several challenges in its implementation, such as limited service time, lack of coordination with homeroom teachers and parents, and low understanding of some teachers about the role of BK in supporting the implementation of the Independent Curriculum. These findings indicate the need to increase the capacity of BK teachers, better cross-sector collaboration, and managerial support from the school so that BK services can function optimally and in line with the spirit of the Independent Curriculum.